The role of alpha-giardin in response to drug treatment in giardia intestinalis - Roslim, Nurul Afiedia (2018)
Giardiasis, which is caused by the intestinal protozoan parasite Giardia intestinalis, affects approximately 280 million people around the world, particularly in children below five years of age. Oral ingestion of as few as ten cysts of G. intestinalis can cause infection in human which lead to complications such as severe dehydration and weight loss. There are several antigiardial drugs available for giardiasis treatment; however, issues such as drug resistance, reinfection and recurrence of symptoms have been highly reported. Thus, the finding for a novel potential drug targets is important to control giardiasis. In this study, we sought to examine the role of alpha-giardins in response to drug treatment in G. intestinalis. Our results showed that G. intestinalis were more susceptible to the action of Mebendazole (MBZ) as the IC50 value for MBZ was 0.06 μM when compared with Metronidazole (MTZ) of 9.177 μM. Trophozoites treated with high concentration of MBZ or MTZ showed significant reduction in viability. The release of reactive oxygen species were not detected in either MBZ or MTZ-treated G. intestinalis. We also found that G. intestinalis treated with 100 μM MBZ or MTZ showed significant upregulated expression of alpha-2 giardin (p ≤ 0.05). In conclusion, alpha-2 giardin could serve as a novel potential target for future drug design and vaccine development.